Ion accumulation in young plants of the ‘green dwarf’ coconut under water and salt stress - Silva, Alexandre Reuber; Bezerra, Francisco Marcus; Lacerda, Claudivan; Miranda, Rafael; Marques, Elton (Revista Ciência Agronômica, 2018)
Water scarcity and salinity are two major limitations on agricultural production. The aim of this study was to investigate the biochemical mechanisms associated with the separate and/or concurrent effects of water deficit and soil salinity on young plants of the ‘green dwarf’ coconut from the responses of ion accumulation (potassium, sodium and chloride) in the leaves and roots. The experiment was carried out in a screened greenhouse in Fortaleza, in the State of Ceará, Brazil. A randomised complete block statistical design was used in a scheme of treatments in subdivided plots, to evaluate the effects of different levels of water deficiency (plots) using different percentages for the replacement of water lost through potential crop evapotranspiration (20, 40, 60, 80 and 100%), associated with sub-plots comprising increasing levels of soil salinity (1.72, 6.25 , 25.80 and 40.70 dS m-1) found in soils collected in the Morada Nova Irrigated Perimeter (Morada Nova/Limoeiro do Norte, Ceará). Under conditions of water scarcity, K+ is maintained and/or accumulated in the leaves; while in the roots, levels are jointly affected by water deficiency and soil salinity, where these stress agents act in an antagonistic way on the K+ content. Conditions of salt stress lead to increases in the levels of Na+ both in the leaves and especially in the roots. The Cl- ion content of the leaves and roots responds to the interaction between water deficiency and salinity, demonstrating synergy in the relationship between stress agents. The accumulation of inorganic solutes in the leaves and roots of the coconut follows the order: Cl- > K+ > Na+.